2007
DOI: 10.1111/j.1365-4632.2007.03071.x
|View full text |Cite
|
Sign up to set email alerts
|

Verruciform xanthoma in recessive dystrophic epidermolysis bullosa Hallopeau‐Siemens

Abstract: 956Case report Verruciform xanthoma in RDEB Murat-Su 1 i 2 et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…In most cases, it involves the oral mucosa, but extraoral presentations have been reported, most often anogenitally . Histologically, VX demonstrates papillomatosis, hyperkeratosis with columnar parakeratosis, and uniform elongation of the rete ridges with foamy histiocytic dermal infiltration . The histiocytes may be subtle, and misdiagnosis as a verruca is possible if they are missed; these histiocytes contain periodic acid‐Schiff‐positive cytoplasmic granules …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, it involves the oral mucosa, but extraoral presentations have been reported, most often anogenitally . Histologically, VX demonstrates papillomatosis, hyperkeratosis with columnar parakeratosis, and uniform elongation of the rete ridges with foamy histiocytic dermal infiltration . The histiocytes may be subtle, and misdiagnosis as a verruca is possible if they are missed; these histiocytes contain periodic acid‐Schiff‐positive cytoplasmic granules …”
Section: Discussionmentioning
confidence: 99%
“…No association has been identified with human papillomavirus despite the papillomatous morphology nor with disorders of lipid metabolism despite the presence of lipid‐laden histiocytes . An etiologic hypothesis is epidermal damage from inflammation or trauma driving psoriasiform hyperplasia, epithelial lipid production, and histiocyte recruitment which become foam cells upon phagocytosis of degenerating keratinocytes and lipid droplets . Ultrastructural studies have demonstrated keratinocyte degeneration …”
Section: Discussionmentioning
confidence: 99%
“…8 Occasionally, cutaneous VX has been described in association with lymphedema, repeated trauma, pemphigus vulgaris, chronic graft versus host syndrome, congenital hemidysplasia with icthyosifom erythroderma and limb defects syndrome, epidermal nevi, dystrophic recessive epidermolysis bullosa, [9][10][11][12] discoid lupus erythematosus, sundamaged facial skin, and solar keratosis. VX is characterized by the presence of acanthosis, hyperkeratosis with columnar parakeratosis, and papillomatosis without architectural atypia and by the presence of a dense accumulation of xanthomatous foamy cells in the papillary dermis that are positive for the macrophage marker CD68.…”
Section: Discussionmentioning
confidence: 99%
“…However, serial studies have failed to find conclusive evidence of HPV infection within VX cells. [9][10][11][12] The observed lesions corresponded to erythematous, verrucous plaques of variable size (from 8 to 12 cm) developing over the sacrum, leg, shoulder, and inguinal region, respectively. The degenerated epithelium might lead to the formation of lipid droplets that would be trapped by dermal cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, no conclusive evidence of the malignant transformation of preexisting VX exists (4); although, there are some reports of no oral VX associated with SCC (12,13). Murat-Susić et al (6) presented a case of VX associated with epidermolysis bullosa and highlighted that the concomitant presence of VX in patients with epidermolysis bullosa could pose an increased risk of SCC occurrence. Drummond et al (10) reported one case of VX associated with carcinoma in situ and high epithelium dysplasia adjacent to SCC, located in the buccal floor.…”
Section: Discussionmentioning
confidence: 99%